(untitled) (Research, Society and Development, 2025)
Objective: To reflect on the management of acute psychological distress in emergency services without specialized mental health support, in light of Madeleine Leininger’s Transcultural Care Theory. Method: A theoretical-reflective study based scientific literature addressing psychological distress, emergency care, mental health, and nursing theories, emphasizing the Transcultural Care Theory. Results: The analysis reveals that, in emergency contexts lacking specialized mental health support, psychological distress is often reduced to biological and behavioral manifestations. The transcultural framework broadens clinical understanding by recognizing values, beliefs, sociocultural contexts, and life experiences as central elements for ethical, humanized, and effective care. Conclusion: The Transcultural Care Theory emerges as a robust framework to guide mental health care practices in emergency settings, particularly in resource-limited scenarios, strengthening comprehensive care, qualified listening, and culturally congruent decision-making.